Violencia y derechos humanos (1993)
"The proceedings of a 1991 Conference organized by the Chilean Human Rights Commission on different aspects of political violence. Includes presentations by leading Chilean political figures (Jorge Arrate, Maria Maluenda, and Genaro Arriagada) and noted academics and professionals (Sergio Garcia, Hugo Früling, Leon Rositcher, Luz Casanave, and Ana Cáceres)"--Handbook of Latin American Studies, v. 57